A cross-sectional study of knowledge, attitude, and practice toward COVID-19 in solid organ transplant recipients at a transplant center in the United States - Wang, Lucas; Abualfoul, Mujahed; Oduor, Hellen; Acharya, Priyanka; Cui, Mingyang; Murray, Anne; Dominguez, Edward; Pagadala, Mangesh (Frontiers in Public Health, 2022)
Objectives Knowledge, attitude, and practices (KAP) have been widely used during times of pandemic to quantify and locate gaps of care during pandemics. Using this tool, we can identify and target populations who underwent solid organ transplant (SOT) to bolster preventative practices in these patients during COVID-19. Materials and methods An institution-based cross-sectional study was conducted between June 1, 2020 and June 30, 2021 on patients who underwent a liver and/or kidney transplant at Methodist Dallas Medical Center in Dallas, Texas, USA. A KAP questionnaire of 26 questions about COVID-19 was designed based on the clinical and community management guidelines published by the WHO. The participant's overall KAP was categorized using Bloom's cut-off point. A KAP domain was considered sufficient if the score was between 60 and 100% and insufficient if the score was <60%. The strength of association was assessed by using odds ratio (OR); only significant independent factors in each tested area were assessed. Results Respondents with children in the household were less likely to have sufficient practices than those who did not [OR = 0.2491, 95% Confidence Interval (0.0893–0.6120), p = 0.001]. We also found that sufficient levels of knowledge correlated with higher likelihood of sufficient levels of practices [OR = 4.94, 95% CI (1.646–14.2159), p < 0.005]. Interestingly, we found that sufficient levels of attitude did not correlate with sufficient levels of practice (p = 0.201). Conclusion Our study found that knowledge and having children in the household correlated with higher levels of practice.